An unusual occurrence of multiple primary malignant neoplasms: a case report and narrative review - Salhab, Rawand Qasim; Ghazaleh, Zeina Ihab; Barbarawi, Wadee; Salah-Aldin, Riyad; Hour, Hani; Sweity, Raghad; Bakri, Izzeddin A. (Frontiers in Oncology, 2024)
Introduction: Multiple primary malignant neoplasms (MPMNs) are cancers presenting distinct pathological types that originate from different tissues or organs. They are categorized as either synchronous or metachronous. Nowadays, the incidence of MPMN is increasing.Patients and Methods: We present a case of a 71-year-old male with a medical history of hepatitis B and a family history of breast and endometrial cancer. The patient reported a nasal tip skin lesion with recurrent bleeding, and the history disclosed lower urinary tract symptoms. Further investigations revealed a coexistence of four primary cancers: basosquamous carcinoma of the nasal lesion, prostatic adenocarcinoma, hepatocellular carcinoma, and clear cell renal cell carcinoma.Results: A multidisciplinary team cooperated to decide the proper diagnostics and therapeutics modules.To the best of our knowledge, the synchronization of these four primary cancers has never been reported in the literature. Even so, Multiple Primary Malignant Neoplasms, in general, are no longer a rare entity and need proper explanations, a precise representation of definition and incidence, further work-up approaches, and treatment guidelines as well.